Bibliometric analysis: Smallholder aggregation models in South Asia - Gupta, Ishika; Veettil, Prakashan Chellattan; Janakiraman, Deepa (TAFSSA, 2024)
This bibliometric analysis examines research trends in smallholder aggregation models across South Asia between 1991-2024. The review analyzed 66 studies through systematic screening of publications from Web of Science and Scopus databases. The findings reveal a strong geographic concentration of research in India (80% of studies) and a predominant focus on contract farming (46%) over other aggregation models. Quantitative methodologies dominated the research landscape (82%), with most studies focusing on economic outcomes like yield, profit, and efficiency rather than social and environmental impacts. The analysis identified key research gaps, including limited coverage of other South Asian countries, insufficient qualitative research on social dynamics, and inadequate attention to inclusiveness and sustainability outcomes. These findings suggest opportunities for more geographically diverse research, methodological diversification, and broader outcome measurements to understand better how different aggregation models can support smallholder agriculture in the region.